Does Islamic Corporate Governance Matter for Risk-Taking? Evidence from Islamic Insurance Companies in Indonesia - Luciana Luthan; Mentari Ritonga (Jurnal Ecogen, 2026)
This article assesses the influence of Shari’ah Supervisory Board (SSB) characteristics on risk-taking behavior in Islamic insurance companies in Indonesia. Specifically, this study analyzes the influence of financial expertise and doctoral educational background of SSB on underwriting risk as a proxy for risk-taking behavior. The study uses panel data from 15 Islamic insurance companies during the period 2014–2024 with a total of 113 observations and analyzed using a Random Effects Model (REM). The results show that financial expertise and doctoral educational background of SSB do not significantly influence underwriting risk. This finding indicates that underwriting risk is more influenced by operational, actuarial, and market conditions than SSB characteristics. The novelty of this study lies in examining the relationship between SSB characteristics and underwriting risk in the Islamic insurance sector, which is still relatively limited compared to the Islamic banking sector. Practically, the results emphasize the importance of strengthening the integration between Shari’ah governance and operational risk management to support more prudent underwriting practices.